2022
DOI: 10.1007/s11082-022-03888-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of a broadband dispersion compensated ultra-high nonlinear photonic crystal fiber

Abstract: A photonic crystal fiber (PCF) with four circular rings of air holes expanded toward the cladding region is proposed. Four circular tiny air hole rings have been used between the air holes in a regular circular PCF to achieve low dispersion (D) and confinement loss (CL).Additionally, the core region is perforated with a rectangular-shaped hole filled with an extremely nonlinear material, gallium phosphide (GaP), to achieve the desired level of nonlinearity. We achieved extremely high nonlinearity and birefring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Lanh et al [27] showed that PCFs containing C 6 H 5 NO 2 cores in circular matrices have lower attenuation and higher nonlinearity compared to square and hexagonal lattices, which have potential applications in SC spectrum generation. A number of research papers on the use of circular PCFs have been published in recent years [32,[34][35][36]. Pandey et al [35] initially proposed a circular PCF with three rectangular holes in the core region filled with GaP and found that the negative dispersion and nonlinearity of this PCF are very high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanh et al [27] showed that PCFs containing C 6 H 5 NO 2 cores in circular matrices have lower attenuation and higher nonlinearity compared to square and hexagonal lattices, which have potential applications in SC spectrum generation. A number of research papers on the use of circular PCFs have been published in recent years [32,[34][35][36]. Pandey et al [35] initially proposed a circular PCF with three rectangular holes in the core region filled with GaP and found that the negative dispersion and nonlinearity of this PCF are very high.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey et al [35] initially proposed a circular PCF with three rectangular holes in the core region filled with GaP and found that the negative dispersion and nonlinearity of this PCF are very high. They further extended the four rings of air holes toward the cladding area interwoven by four tiny air hole rings to acquire low dispersion and confinement loss [36]. As a result of these enhanced optical features, the designed PCFs are capable of effective dispersion compensation, polarization-maintaining, and SCG.…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication techniques have also improved, enabling the production of larger and more complex structures with greater accuracy. Photonic crystals are being integrated with other technologies, including microfluidics, optoelectronics, and sensors, to create more advanced devices with multiple functionalities [3,4].…”
Section: Introductionmentioning
confidence: 99%